Determination of interfacial adhesive properties for polymeric film by blister test - Wang, Z.; Ma, Z.; Zhou, Y.; Lu, Chunsheng (Elsevier, 2013)
The interfacial adhesive properties of polypropylene/stainless steel were studied by the blister test. The polypropylene film with a squared free-standing window was pressured by oil from one side of film. The corresponding deformation field was observed by a digital speckle correlation method. The experimental results show that the squared film deforms and debonds from stainless steel with the increase of pressure. The debonding of the squared film in initiates from the center of edge and extends to the corner, and then the deformation of film evolves from square to circle shape. The interfacial adhesive energy of polypropylene/stainless steel is (22.60±1.55) J/m2, which is in agreement with that measured by film with a circular window.